GROWTH RESPONSE AND YIELD OF SWEET CORN (Zea mays saccharata Sturt) AGAINST MIRACLE GRO AND MANURE FERTILIZER APPLICATION - Darmawan Pranajaya; Cik Zulia; Safruddin Safruddin (Bernas : Jurnal Penelitian Pertanian, 2018)
The research was conducted in the Tanjung Sari village, Sei Dadap, Asahan, North Sumatraprovince with a height of ± 17 m above sea level, tipy of climate C (oldeman). This study wasconducted in Mey to July 2017. The study design was a Randomized Block Design (RBD)Factorial consisting of 12 treatment combinations, each 4 levels application of Miracle Grofertilizer is: M0 = 0 g Miracle Gro/l water (control), M1 = 1 g Miracle Gro/l water, M2 = 2 g Miracle Gro/l water, M3 = 3 g Miracle Gro/l water and 3 levels of manure fertilizer is: K0 = 0 tons/ha (control), K1 = 15 tons/ha (4,5 kg/plot), K2 = 30 tons/ha (9 kg/plot). The results showed that giving Miracle Gro of concentration 3 g/l water (M3) on sweet corn can increase the growth of crop height age of 2, 4 and 6 Weeks After Planting (WAP); stem diameter ages 6 WAP; the number of leaf age 2, 4 and 6 WAP; weight of cob weighs per plot; weight of cob without any weight per plot. Giving manure fertilizer up to dose 30 tons/ha (K2) on sweet corn can increase the growth of crop height age of 2, 4 and 6 WAP; stem diameter ages 6 WAP; the number of leaf age 2, 4 and 6 WAP; weight of cob weighs per plot; weight of cob without any weight per plot. Interaction of giving Miracle Gro and manure fertilizer very significant effect on plant height, weight of cob weighs per plot; weight of cob without any weight per plot. The interaction is best obtained in treatment M3K2 (3 g Miracle Gro/l water and 30 tons/ha of manure fertilizer).